Analysis of 5G Cellular Network Architecture - Fengyi Yang; Jianmin Zhang; Weiliang Xie; Min Wang; Haining Wang (Dianxin kexue)
In order to satisfy the various requirements of future network services，5G system should not only broaden the spectrum bandwidth and improve the spectrum efficiency through exploiting new technologies，but also need a novel wireless network architecture. Therefore，the key features of 5G cellular network architecture based on the demands of future network were analyzed and concluded. Meanwhile，a novel 5G architecture was proposed based on the software defined networking（SDN）and network function virtualization（NFV）. In addition，the problems and challenges of the proposed 5G cellular network architecture were also discussed and analyzed.